THE SOCIETY OF SPECTACLE: AN ISLAMIC PERSPECTIVE - Halim, Hendra; Nisva, Raisa Ullya; Humaira, Radhia (International Journal of Kita Kreatif, 2024)
This research explores the relevance of Guy Debord's concept of the "society of the spectacle" in the modern era, particularly from an Islamic perspective. The study aims to assess the impact of media-driven spectacles on social reality and individual well-being, and to provide policy recommendations to mitigate their negative effects. The methodology involves a critical analysis of Debord's theory alongside Islamic teachings to draw parallels and contrasts. The findings reveal that the society of the spectacle creates a superficial reality where media and entertainment industries dominate social perceptions, leading to alienation, dissatisfaction, and a focus on appearances rather than substance. From an Islamic viewpoint, this phenomenon can be seen as a form of fitnah (temptation or trial) that diverts individuals from spiritual and moral truths. Islam criticizes behaviors such as excessive consumption (israf) and arrogance promoted by spectacles, emphasizing simplicity, humility, and the pursuit of genuine spiritual and moral well-being. The study identifies significant negative impacts of the spectacle on spiritual and moral development, including the erosion of moral values, encouragement of excessive consumption and arrogance, and a loss of deeper meaning in life. To address these issues, the research recommends policies focused on enhancing media literacy, promoting lifestyles that emphasize simplicity and sustainability, integrating spiritual and moral education into curricula, ensuring media content promotes positive values, and encouraging community-based initiatives that strengthen real social interactions and mutual support.